34.9k views
4 votes
Help me pls asap. Evaluate f−g+(−2) where f=−3.005 and g=4.7

1 Answer

0 votes

Final answer:

To evaluate f - g + (-2), substitute the values of f and g into the expression and simplify to find the result.

Step-by-step explanation:

To evaluate the expression f - g + (-2), we substitute the given values of f and g into the expression:

f - g + (-2) = -3.005 - 4.7 + (-2)

Next, we simplify the expression by performing the subtraction and addition:

-3.005 - 4.7 + (-2) = -7.705 + (-2) = -9.705

Therefore, the value of f - g + (-2) is -9.705.

User Sayooj V R
by
5.7k points